STRATEGI KESANTUNAN POSITIF DALAM TINDAK TUTUR PADA NOVEL BIDADARI-BIDADARI SURGA KARYA TERE LIYE - Rahmi Rahmi; Shafruddin Tadjuddin (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2017)
AbstractThis study aims to gain an in-depth understanding of the positive politeness strategy of speech acts in Tere Liye's Bidadari-Bidadari Surga novel. This research is a qualitative research with content analysis method. The data were collected through literature study and polite observation in speech acts on Tere Liye's novel Bidadari-Bidadari Surga. The data analysis uses Brown and Levinson's politeness theory. These findings indicate that Tere Liye's novel Bidadari-Bidadari Heaven contains a positive politeness strategy. The strategy of positive politeness includes fifteen positive politeness strategies and in the form of thirty-nine kinds of mannerisms spoken by the characters of the story.Keywords: Strategy of positive politeness, speech acts, novel